Technical and economical assessment of voltage control strategies in distribution grids. (24th January 2013) - Stetz, Thomas; Kraiczy, Markus; Braun, Martin; Schmidt, Sebastian
ABSTRACT Technically effective and economically efficient voltage control is a major issue in distribution systems with high amounts of installed capacity from dispersed generators, such as photovoltaic. In this paper, the results of an encompassing cost–benefit analysis for different voltage control strategies are presented. The investigated voltage control strategies comprise two different reactive power control methods and one combined reactive power/active power control method, each applied by inverters of utility scale photovoltaic systems. The results are gained by performing 12‐month root‐mean‐square simulations with a 1 min resolution, using the model of a real distribution grid as well as complex generation and load models. The simulations show that local reactive power provision methods as well as temporal active power output curtailment methods are capable of reducing the necessity of a voltage‐driven grid reinforcement. However, the economic benefit of those voltage control strategies highly depends on the parameterization of the respective control algorithm. Copyright © 2013 John Wiley & Sons, Ltd.